2008
DOI: 10.1111/j.1365-2265.2007.03138.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin, adiponectin, IGFBP‐1 levels and body composition in small for gestational age born non‐obese children during prepubertal ages

Abstract: SGA children with CUG and with no obesity have higher insulin levels compared to AGA children. Both SGA birth and recent size seem to have an effect on serum adiponectin levels in childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 34 publications
3
32
0
2
Order By: Relevance
“…In addition, serum insulin concentrations were significantly lower and there was a trend for lower HOMA-IR in the SGA than AGA children, which was explained by their lower BMI. However, there are other studies showing higher fasting insulin levels also in those SGA children who are thinner than their controls [20]. Interestingly, HOMA-IR was also significantly lower in the LGA than AGA girls.…”
Section: Discussionmentioning
confidence: 79%
“…In addition, serum insulin concentrations were significantly lower and there was a trend for lower HOMA-IR in the SGA than AGA children, which was explained by their lower BMI. However, there are other studies showing higher fasting insulin levels also in those SGA children who are thinner than their controls [20]. Interestingly, HOMA-IR was also significantly lower in the LGA than AGA girls.…”
Section: Discussionmentioning
confidence: 79%
“…By contrast, two previous studies demonstrated lower adiponectin concentrations in IUGR and proposed that this down-regulation may be a predisposing factor for later development of insulin resistance/metabolic syndrome (110,111). Interestingly, in support of this view, adiponectin levels in IUGR children were particularly low in those who showed postnatal catch-up growth, compared with the levels in IUGR children who remained small during childhood (112,113). This may indicate that the low adiponectin levels in IUGR infants may actually predict the subsequent development of visceral fat and insulin resistance (112).…”
Section: Adiponectin In Iugrmentioning
confidence: 85%
“…In fact, insulin level was one of the major determinants of ghrelin levels in our study. We, along with other investigators, have shown that SGA born children may have higher insulin levels in early childhood in spite of normal BMI levels (20,(26)(27)(28), and it has been shown that ghrelin has inverse correlation with insulin (5).…”
Section: Discussionmentioning
confidence: 99%